Profil Sosial Ekonomi Pedagang Durian di Desa Sabbang Kecamatan Sabbang Kabupaten Luwu Utara - Samat, Abdul; Invanni, Ichsan; Badwi, Nasiah (LaGeografia, 2021)
This research aims to: (1) Know the description of the social life of durian traders in Sabbang Village, (2) Know the description of the economic life of durian traders in Sabbang Village. This type of research is descriptive qualitative research with a total target of 14 traders. This research was conducted in Sabbang Village, Sabbang District, North Luwu Regency. The data were collected by means of observation, questionnaires and interviews, and documentation. The data analysis used reduction techniques, data presentation, and conclusions. The results showed that: (1) The conditions of social life of traders were varied, the youngest was 22 years old and the oldest was 55 years old, consisting of nine males and five females. Thirteen traders were married and one was widowed. Education levels from SD, SMP and SMA. The four traders live in harvester houses, three semi-permanent houses and six non-permanent houses. (2) The economic conditions of durian traders also vary. The main job of most traders is farmers, with an income of Rp. 900,000 - Rp. 2,500,000 per month. Meanwhile, income from durian trading ranges from Rp. 6,000,000 - Rp. 19,000,000 per season. Trading starts in December and January, ends in March and April. Trading activity starts at 06:00 AM to 09:00 AM and ends when the durian is sold out. The contribution of durian trade for economic entrepreneurs is quite high because they get a fairly large income compared to their main work.